Provocative Questions in Behavioral Medicine and the Acceleration of our Science. Issue 12 (8th January 2021) - Diefenbach, Michael A; Phillips, Alison; Bullock, Lindsay
Abstract : A visioning initiative among members of SBM has identified new areas of investigations, such as behavioral medicine's need to address climate change, gun violence and science communication. These areas emerged along-side traditional areas of behavioral medicine such as decreasing health inequity and integrating behavioral medicine into health care systems.